(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Manual management of sales, inventory, and expenses in small retail establishments often results in inaccurate calculations, delayed transactions, inconsistent stock tracking, missing records, and challenges in report generation. These issues can negatively affect business operations, financial monitoring, and decision-making processes. To address these challenges, this study developed SmartPOS Budgeteer, a Python-based, Graphical User Interface (GUI)-driven system that integrates Point-of-Sale (POS), inventory management, and expense tracking functionalities into a single platform. The system was designed and implemented using Object-Oriented Programming (OOP) principles to ensure modularity, maintainability, scalability, and efficient code organization. The graphical user interface was developed using Tkinter, providing an intuitive and user-friendly environment for business owners and staff. Data management and storage were implemented through SQLite and MySQL databases to ensure secure, accurate, and permanent record keeping. The system includes modules for sales processing, inventory monitoring, expense recording, refund management, activity logging, and report generation. Automated calculations and real-time database updates help minimize human errors while improving operational efficiency. A system development approach based on the Software Development Life Cycle (SDLC) was utilized throughout the planning, design, implementation, testing, and deployment phases. Functional testing was conducted to evaluate the performance, reliability, and accuracy of each module. Results showed that the system successfully processed sales transactions, updated inventory records, recorded expenses, handled refund transactions, validated user inputs, and generated accurate reports. All test cases passed, demonstrating the reliability and effectiveness of the system in supporting retail business operations. The findings indicate that SmartPOS Budgeteer provides a unified, efficient, and user-friendly solution for small retail establishments. By integrating POS, inventory, and expense management functionalities, the system improves accuracy, accountability, record organization, and business decision-making. Furthermore, the implementation of OOP principles and database integration contributes to system maintainability, data integrity, and long-term usability. The study demonstrates the potential of Python-based business management systems in enhancing operational productivity and supporting the digital transformation of small retail enterprises.